Relationship between types of organization with the quality of soft-scape construction work in Malaysia - Ab Sani, Jasasikin; Ahmad Sharip, Nur Athirah; Othman, Noriah; Mohd. Hussain, Mohd. Ramzi (Association of Malaysian Environment-Behaviour Reseachers (AMER), 2017)
This paper intends to focus on the relationship between types of organisations with the issues of quality of soft-scape construction work. The types of organizations are consultant, contractor, developer, government agency, and educational institution. This research will be using the mix method approach. Chi-square analysis was also performed to find the significant level of relationship between the respondents. Respondents of the survey are among Landscape Architects listed in ILAM directory. The study managed to conduct the questionnaire on 225 persons. This paper was identified the significant difference of the respondents from different type of organisations with the issues of soft-scape construction quality.